2021
DOI: 10.3390/cancers13030491
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Lysyl Oxidase Family Meditated Matrix Cross-Linking as an Anti-Stromal Therapy in Solid Tumours

Abstract: The lysyl oxidase (LOX) family of enzymes are a major driver in the biogenesis of desmoplastic matrix at the primary tumour and secondary metastatic sites. With the increasing interest in and development of anti-stromal therapies aimed at improving clinical outcomes of cancer patients, the Lox family has emerged as a potentially powerful clinical target. This review examines how lysyl oxidase family dysregulation in solid cancers contributes to disease progression and poor patient outcomes, as well as an evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 170 publications
(254 reference statements)
0
55
0
Order By: Relevance
“…The present study sheds new insight into the role that the tumor ECM – established by LH2-mediated cross-links – plays in promoting HNSCC metastasis. Several studies have suggested that increased total collagen cross-links resulting from upregulation of LOX family members are associated with poor prognosis in patients with breast, lung, and oral cancers [ 28 , 42 , 48 , 50 ]. However, here we show that knockdown of LH2 alone is sufficient to blunt invasion and metastasis despite robust cellular expression of LOX and LOXL2.…”
Section: Discussionmentioning
confidence: 99%
“…The present study sheds new insight into the role that the tumor ECM – established by LH2-mediated cross-links – plays in promoting HNSCC metastasis. Several studies have suggested that increased total collagen cross-links resulting from upregulation of LOX family members are associated with poor prognosis in patients with breast, lung, and oral cancers [ 28 , 42 , 48 , 50 ]. However, here we show that knockdown of LH2 alone is sufficient to blunt invasion and metastasis despite robust cellular expression of LOX and LOXL2.…”
Section: Discussionmentioning
confidence: 99%
“…In various tumors, overexpression of LOX induced by a hypoxic (45). Targeting LOX family-mediated matrix cross-linking as an anti-matrix therapy for solid tumors (46). Similarly, Setargew et al…”
Section: Discussionmentioning
confidence: 99%
“…De Vita et al reported: Lysyl oxidase engineered lipid nanovesicles for the treatment of triple-negative breast cancer ( 45 ). Targeting LOX family-mediated matrix cross-linking as an anti-matrix therapy for solid tumors ( 46 ). Similarly, Setargew et al found that radioactive LOX-trackable nanoparticles (LOX ab-NPs) can be used as chemotherapy carriers for combined targeted radiotherapy and chemotherapy in clinical oncology ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…The LOX family can be classi ed into two groups based on the structure of their N-terminal domains: LOX and LOXL1 have a propeptide at their N-terminal, whereas LOXL2, LOXL3, and LOXL4 have four scavenger receptor cysteine-rich domains [19]. The LOX family gene subtypes (LOX, LOXL1-4) are all amine oxidases and contain a highly conserved C-terminal binding domain that forms a special lysine tyrosylquinone cofactor-moiety after binding to the copper ion cofactor [20]. These family genes are critical enzymes that regulate the crosslinking of elastin and collagen to have a regulatory role in ECM assembly [21], while the dysregulation of ECM may disrupt the function or structure of the arterial wall, and may be a risk factor in the pathogenesis of aSAH [14,22].…”
Section: Discussionmentioning
confidence: 99%